After rules of associativity and precedencce, if we think of last expression as E1 - E2, if we evaluate E1, then answer is 3, but if we evaluate E2 first, we would be getting 2 as the minimum answer. -> explained below.

t1 = e*f

t1 = t1+a

t2 = g+h

t2 = t1 - t2

t1 = a*b

t1 = t1*c

t1 = t1+d

t1= t1-t2

Shouldn't minimum answer be 2? Am i doing anything wrong here?

t1 = e*f

t1 = t1+a

t2 = g+h

t2 = t1 - t2

t1 = a*b

t1 = t1*c

t1 = t1+d

t1= t1-t2

Shouldn't minimum answer be 2? Am i doing anything wrong here?